PERPANJANGAN SURAT IZIN MENGEMUDI MELALUI MOBIL LAYANAN DAN SIM CORNER - Suhartono, Slamet (DiH: Jurnal Ilmu Hukum, 2015)
Abstract: In order to realize the welfare, the government continues its efforts to improve the public service, including the extension of a driver's license. Driver's license renewal service is done at counters the common crowd, like in the Mall, Supermarket, Roads, and so forth without being followed by the specified requirements, including not doing medical tests. In the perspective of elimination of administrative law requirements, in particular health condition is not in accordance with nature and permission functions. Because a person's health condition may change at any time decreased, and in a certain degree could endanger driving license holders, as well as other road user community. For the retest medis is essential in driver's license renewal.Key Word: driving license, health condition, endangering